2020
DOI: 10.1002/tre.733
|View full text |Cite
|
Sign up to set email alerts
|

Clinical teaching fellows: a mutually beneficial relationship

Abstract: Clinical teaching fellow (CTF) jobs give junior doctors the opportunity to develop their mentoring and teaching skills, yet awareness of the posts remains low. Here the authors describe what being a CTF entails and the benefits it can offer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…In accordance with other studies, the CTFs were found to be using the opportunity to decide upon their future careers, 8,9,13 enhance their CV, 6,9,14 develop skills as an educator 8,9,14 and take some time for their lives outside of clinical practice. 6,7,13 Given that 43% of trainees are uncertain about their specialty choice after Foundation training, 15 pausing to consider career options is understandable.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In accordance with other studies, the CTFs were found to be using the opportunity to decide upon their future careers, 8,9,13 enhance their CV, 6,9,14 develop skills as an educator 8,9,14 and take some time for their lives outside of clinical practice. 6,7,13 Given that 43% of trainees are uncertain about their specialty choice after Foundation training, 15 pausing to consider career options is understandable.…”
Section: Discussionsupporting
confidence: 86%
“…One established route that UK trainees take is to become a Clinical Teaching Fellow (CTF), 5 with those taking this route citing that they do so for the same reasons as mentioned above 6–9 . Typically, these 1‐year posts combine delivering undergraduate medical education and providing clinical care, although there are varying contractual arrangements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is often opportunity to complete formal part-time qualifications in medical education, alongside other teaching and clinical responsibilities. 20 Given these opportunities, CTFs have the ability to develop as educators, doctors and individuals. 21 …”
Section: Discussionmentioning
confidence: 99%